Seventh International Symposium on Signal Processing and Its Applications, 2003. Proceedings. 2003
DOI: 10.1109/isspa.2003.1224818
|View full text |Cite
|
Sign up to set email alerts
|

Blind separation of speech mixtures based on nonstationarity

Abstract: This paper presents a method for blind separation of convolutive mixtures of speech signals, based on the joint diagonalization of the time varying spectral matrices of the observation records and a novel technique to handle the problem of permutation ambiguity in the frequency domain. Simulations show that our method works well even for rather realistic mixtures in which the mixing filter has a quite long impulse response and strong echos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(107 citation statements)
references
References 4 publications
1
106
0
Order By: Relevance
“…The non-stationarity was first taken into account by Matsuoka et al (1995). This problem has been studied by Parra and Spence (2000a) and Pham et al (2003). It was shown that decorrelation is able to perform the BSS task for wide class of source signals.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The non-stationarity was first taken into account by Matsuoka et al (1995). This problem has been studied by Parra and Spence (2000a) and Pham et al (2003). It was shown that decorrelation is able to perform the BSS task for wide class of source signals.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In this paper, we only consider the permutation problem, where the order of the recovered source components at each frequency bin may not be consistent with each other (e.g. ½ [26,30] utilizes the continuity of the spectral components in adjacent frequency channels while [27,28] use direction of arrival estimation, [31] combines both previous techniques, and [32] utilizes statistical signal models. However, the performance of these algorithms can be degraded by acoustical noise.…”
Section: Scaling and Permutation Indeterminacymentioning
confidence: 99%
“…For the FD-BSS, the joint approximate diagonalization method proposed in [30] is used for source separation at each frequency bin. Note that the same ICA algorithm was used here for the contrast methods [30,33] in our comparisons in Section 5.2.2.…”
Section: An Examplementioning
confidence: 99%
See 2 more Smart Citations